2013
DOI: 10.1159/000347087
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Treatment Response and the Effect of Independent Component Neurofeedback in Obsessive-Compulsive Disorder: A Randomized, Sham-Controlled, Double-Blind Study

Abstract: Aims: The goal of this study was to assess the effect of independent component neurofeedback (NFB) on EEG and clinical symptoms in patients with obsessive-compulsive disorder (OCD). Subsequently, we explored predictors of treatment response and EEG correlates of clinical symptoms. Methods: In a randomized, double-blind, parallel design, 20 inpatients with OCD underwent 25 sessions of NFB or sham feedback (SFB). NFB aimed at reducing EEG activity in an independent component previously reported abnormal in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
3
34
1
Order By: Relevance
“…Interestingly, a recent human DBS study in OCD patients showed that NAc-DBS reduced low-frequency EEG oscillations recorded over the frontal cortex during symptom provocation as well as resting-state functional connectivity (fMRI) between NAc and the prefrontal cortex (Figee et al, 2013a). Our previous as well as other studies reported medial frontal low frequency EEG excess in OCD patients (e.g., Kopřivová et al, 2011, 2013a,b). These findings support the predictive validity of the QSM because similar to DBS, quinpirole sensitization probably inhibits NAc.…”
Section: Predictive Validity Of the Qsmsupporting
confidence: 68%
See 1 more Smart Citation
“…Interestingly, a recent human DBS study in OCD patients showed that NAc-DBS reduced low-frequency EEG oscillations recorded over the frontal cortex during symptom provocation as well as resting-state functional connectivity (fMRI) between NAc and the prefrontal cortex (Figee et al, 2013a). Our previous as well as other studies reported medial frontal low frequency EEG excess in OCD patients (e.g., Kopřivová et al, 2011, 2013a,b). These findings support the predictive validity of the QSM because similar to DBS, quinpirole sensitization probably inhibits NAc.…”
Section: Predictive Validity Of the Qsmsupporting
confidence: 68%
“…The ACC is of particular interest in this context. Functional hyperactivity and decreased volume in this area has been shown repeatedly by converging evidence from different methods (Kopřivová et al, 2011, 2013a,b) yet no study has been aimed to assess the effects of cingulotomy in the QSM.…”
Section: Predictive Validity Of the Qsmmentioning
confidence: 99%
“…Two multicentric studies were conducted in Germany, Italy, USA, and Chile (Buyukturkoglu et al, 2015), and the Czech Republic and France Table 1 Summary of demographic and clinical information of the studies included for systematic reviewing. ( Koprivová et al, 2013). The other works were performed in Turkey (Sürmeli and Ertem, 2011), Iran (Barzegary et al, 2011), Canada (Mills and Solyom, 1974), China (Deng et al, 2014), and USA (Hammond, 2004(Hammond, , 2003LeVine, 1983;Scheinost et al, 2014).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…EEG neurofeedback training in generalized anxiety disorder (GAD) [98-99], and obsessive-compulsive disorder (OCD) [100] has shown increased effectiveness compared to relaxation biofeedback and “placebo” neurofeedback, respectively. However, it is unclear whether neurofeedback has any therapeutic effect in alleviating disease-specific symptoms in anxiety disorders.…”
Section: Application Of Bcis As An Intervention In Psychiatric Disordersmentioning
confidence: 99%